Nanoarchitectonics through supramolecular gelation: formation and switching of diverse nanostructures. Issue 1 (7th November 2018) - Sang, Yutao; Liu, Minghua
Abstract : The formation and switching in gel systems provide supramolecular gelation many possibilities to obtain diverse nanoarchitectures. Abstract : Supramolecular gels are currently an important class of soft materials that are attracting great interest. The gelation process has been proven to be a powerful approach for the construction of diverse and uniform architectures. Generally, these architectures are on the nanoscale and hierarchically self-assembled from small molecules. Nanoarchitectonics tries to bridge the gap between molecules and nanostructures, while supramolecular gelation provides a good platform to realize such a goal. While the design of the gelator molecules and the function of the gel are important topics, here, we focus on how small molecules can be fabricated into nanostructures through gelation, which is in fact the connection between the microstructures to the macroscopic functions. We showed meritorious examples of typical architectures constructed through the supramolecular gelation process. Then some examples showing the transformation or switching between different nanostructures are presented, which reflected the unique responsiveness of the gel system. Through these two key parts, we hope to provide useful insights into the design and control of functional nanoarchitectures via supramolecular gelation.